(untitled) (Indian Journal of Child Health, 2014)
Although tuberculous aortitis is fairly common in adults, tuberculous mycotic aneurysm of aorta is rare withinvolvement of aortic root being very uncommon. The diagnosis depends on a combination of clinical criteria,including persistent fever and bacteraemia and echocardiographic confirmation. Because of the rarity of aorticroot abscess in children, there is no consensus on a treatment strategy. We describe a 10-year-old male whopresented with fever, abdominal pain and headache, and was found to have disseminated tuberculosis and aortic root abscess with mycotic aneurysm. Due to the presence of evidence of tuberculosis elsewhere in the body (multiple tuberculomas in brain, granulomas in liver, lichen scrofulosorum over abdomen), therapy with antituberculous drugs was started to which the patient responded partially, but later died suddenly at home.